THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMP NEGERI 3 TAMBANG - Rizola, Shinta; Purwanti, Tri Indah; Novitri, Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This present study was aimed to find out whether there was a correlation between vocabulary mastery and reading comprehension of the second year students of SMP Negeri 3 Tambang. The population was the second year students of SMP Negeri 3 Tambang. The sample was chosen by using cluster random sampling and there were VIII4 and VIII5 as the samples. Vocabulary test was used to know the students’ vocabulary mastery and reading comprehension test was used to know the students reading comprehension in descriptive text. The obtained data were analyzed by using Pearson Product Moment’s Formula which was assisted by SPSS 23.00 program. The results revealed that the coefficient correlation was higher than the critical value of r-table (0.739 > 0.254). Therefore, the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted. In conclusion, there was a positive correlation between vocabulary mastery and reading comprehension of the second year students of SMP Negeri 3 Tambang. The obtained determination coefficient (R square) is 0.545 or 54%. This means that vocabulary clarify only 54% toward reading comprehension. While the rest 46% (100%-54%) is probably due to other factors which are not involved in this research’s variables.Key Words: Correlation, Vocabulary Mastery, Reading Comprehension